Identifikasi dan Prevalensi Endoparasit pada Ikan Bawal Bintang (Tracinhotus Blochii) di Lokasi Budidaya Perikanan Teluk Bintan - syafitri filzah; Tengku Said Raza'i; Rika Wulandari (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2018)
The aim of this study were to identify the type of endoparasites and the internal organ prevalence invasion on silver pompano (Tracinhotus blochii). This study was conducted by in vitro. The procedures consist of the random fish sampling was about 5% in 3 culture area, then the purification of endoparasite done by isolation technique. The process of endoparasites identification based on the manual identification by Kabata (1985) and Rigby (1998). This study obtained one genus of Camallanus in the intestine with a 4,4% prevalence.